The Channel ecosystem, a cross-roads of anthropogenic pressures and scientific studies: Lessons learned from the European INTERREG IV projects (2009–2015). (January 2016) - Evariste, Emmanuelle; Claquin, Pascal; Robin, Jean-Paul; Auber, Arnaud; McQuatters-Gollop, Abigail; Dauvin, Jean-Claude
Abstract: The English Channel hosts a high density of human activities, which result in strong pressures and impacts on its marine ecosystem. The European Union's INTERREG programme funds projects to promote sustainable development through ecosystem-based management and the development of socio-economic services in the Channel region. An analysis of the themes studied during INTERREG IVA projects to date reveals both gaps that should be addressed in the future, as well as good practices that should be maintained and promoted. This analysis was used to provide advice and recommendations on knowledge gaps which may form the foundation of future projects for European programmes such as those in the next INTERREG project call (2015–2020). Highlights: The Channel marine ecosystem is an area subjected to intense human-induced pressures. INTERREG projects promote sustainable development through ecosystem-based management. Analysis of INTERREG IVA projects reveals gaps and good practices. Recommendations to address these gaps in future European projects are delivered.